Relationship Between Gallbladder Distension and Lipid Profiles in Kawasaki Disease - Kim, Ki-Won (The Korean Society of Cardiology, 2010)
BACKGROUND AND OBJECTIVES: Kawasaki disease (KD) is an acute systemic vasculitis in children which causes coronary arterial dilatation (CAD) and gallbladder distension (GBD). There is a dearth of investigating the relationship between the severity of KD and GBD with lipid profiles. SUBJECTS AND METHODS: A total of 80 patients with 'complete KD' who were diagnosed from January 2005 to May 2009 was enrolled in this study. Serum cholesterol {total, high density lipoprotein-cholesterol (HDL-C) and low density lipoprotein-cholesterol (LDL-C)}, triglyceride (TG), complete blood count, inflammation markers {erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP)} were measured at the time of admission during febrile period. Echocardiography and abdominal sonogram were performed in all patients to determine CAD and gallbladder size. According to GBD, patients with KD were classified as patients with GBD and patients without GBD. Between two groups, demographic and clinical data were analyzed. RESULTS: The serum level of LDL-C was significantly lower in patients with GBD (p=0.03) compared with patients without GBD or febrile control. There was no significant difference in inflammatory indices between patients with GBD and patients without GBD. GBD was not significant risk factor of CAD in this study (odds ratio=2.0, 95% confidence interval=0.82-5.3, p=0.16). CONCLUSION: This is the first study that highlights the relationship between the GBD and lipid metabolism in patients with KD. This study provides clinical insights about potential mechanism underpinning the relationship between the GBD and lipid metabolism.